ANALISIS USAHA PETERNAKAN AYAM BROILER POLA KEMITRAAN INTI-PLASMA (Studi Kasus Peternak Plasma PT. Bilabong di Kecamatan Limpung Kabupaten Batang) - Andi Kurnianto; Endah Subekti; Eka Dewi Nurjayanti (MEDIAGRO, 2018)
This research proposes to study production cost, revenue, income, BEP, R/C, and price changes analysis of broiler chicken farming business at PT Bilabong. The method of location determination was held by purposive method. The respondents sample determination method was census with 12 plasma farmer. The research result showed that the production cost average is Rp 223,737,701. Revenue average is Rp 268,247,430 and income average is Rp 44,509,729. The BEP (Unit) is Rp 13,375/kg, the production farmer average 16,467 kg. The BEP (Price) is Rp 15,465/kg, sale farmer average at Rp 16,290/kg. This result showed that broiler chicken business at plasma farmers of PT Bilabong plasma farmers reached higher value than BEP of unit and BEP of price. R/C value showed 1.2. The critical point analysis of price changes was 5% and it is mean that if broiler chicken price lower than 5%, so that the farmers will undergo a loss. Based on the income analysis, BEP and RC estimation, it can be definitely concluded that the plasma broiler chicken farming at PT Bilabong in Limpung district Batang regency is profitable and worth the effort.Keywords: Broiler, Business Analysis, Partnership, BEP, R/C